Analysis of job burnout in people working in sports in the universities of Baghdad - Nasser, Ali Jamel; Hussein Alwan, Qutaiba; Salman Dawood, Mohannad (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The objective of this research was to analyze job burnout in people working in sports in the universities of Baghdad. The researchers used the descriptive approach with survey method, and the sample was composed of 290 sports activity workers. The researchers defined the scale and procedures and applied them to the research sample. The data obtained were processed and interpreted to obtain conclusions. A high level of job burnout was found in the participants of this study. To solve this problem, the authors think that it would be recommendable that people working in sports in the universities of Baghdad are given the opportunity to develop their abilities and are involved in decision-making.